El proceso enseñanza de la Matemática en los estudiantes con necesidades educativas especiales asociadas a la discapacidad en la Unidad Educativa “Ramón Barba Naranjo”, año lectivo 2020-2021. - Balseca Coba, Sandra Ipatia (2021)
The present investigation was framed in a “Guide of ludic strategies in the process of teaching Mathematics for the development of logical thinking in students with Special Educational Needs associated with disability Intellectual in the Educational Unit "Ramón Barba Naranjo", the methodology used was with a qualitative approach where the problem was detected. Quantitatively applied the survey method and statistics to determine numerical results, the existence of alternatives directed to the teaching process of the Mathematics in students with special educational needs associated with disability. The study was carried out in the place under investigation due to the statement of the problem that describes the need of teachers to improve the Mathematics teaching process, through a proposal. This led to the design of a playful strategy guide with a set of inclusive games, the teachers in the area of Mathematics, considered as an instrument for the strengthening the development of logical thinking immersed in adaptations curricular. It was validated by the criteria of experts with sufficient experience in the educational field of Mathematics, therefore, this guide turned out to be feasible, from the validation of the set of inclusive games: Traffic Light, Creating Landscapes, Figures Geometric, Threader, Smart Rabbit, Yaquis, Decompose Numbers, Clown and Positional Location for the teaching of Mathematics in students with educational needs associated with intellectual disability.